Method for preparing multi-heterojunction electrocatalyst by recycling waste lithium ion battery electrode material, multi-heterojunction electrocatalyst and application of multi-heterojunction electrocatalyst

By recycling waste lithium-ion battery electrode materials, and using gradient heating and high-voltage electrospinning technology to prepare multi-heterojunction electrocatalysts, the problem of high recycling costs of rare metals in waste lithium-ion batteries is solved, and low-cost and efficient recycling is achieved. Efficient electrocatalytic performance.

CN119481408APending Publication Date: 2025-02-18SUZHOU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411696308.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to recover rare metals in waste lithium-ion batteries at low cost, environmentally friendly and efficiently, such as cobalt, nickel, manganese, titanium, etc., and the cost of precious metal catalysts in electrolytic cells is high.

Method used

By recycling waste lithium-ion battery electrode materials, a multi-heterojunction electrocatalyst is prepared, and a spinning film with high electrocatalytic activity is formed using gradient temperature-raising treatment and high-voltage electrospinning technology.

Benefits of technology

It realizes the low-cost, environmentally friendly and efficient recycling of rare metals in waste lithium-ion batteries, and prepares efficient non-precious metal electrocatalysts for electrolyzing oxygen evolution reactions, showing excellent catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481408A_ABST
    Figure CN119481408A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a multi-heterojunction electrocatalyst by recycling a waste lithium ion battery electrode material, the multi-heterojunction electrocatalyst and application of the multi-heterojunction electrocatalyst. The invention provides an electrode material recycled from a waste lithium ion battery electrode. Carrying out ball milling on the recovered electrode material, adding a solvent and a nitrogen-containing polymer, and stirring to prepare a spinning solution; performing high-voltage electrostatic spinning on the obtained spinning solution to obtain a spinning film; and placing the spinning film in a heating container, and carrying out gradient heating treatment in an inert atmosphere to obtain the multi-heterojunction electrocatalyst. The method disclosed by the invention has the characteristics of simplicity in synthesis, convenience in operation, wide application range and the like, the preparation condition is mild, the method is simple and easy, special equipment is not needed, the cost is relatively low, and a road is paved for quickly and efficiently recycling the waste batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a method for recycling waste lithium-ion battery electrode materials to prepare a multi-heterojunction electrocatalyst, a multi-heterojunction electrocatalyst and applications thereof. Background Art

[0002] At present, new energy vehicles are developing rapidly, and the continuous generation of waste batteries has caused environmental pollution and waste of resources. Waste batteries are rich in post-transition metals. The current waste battery recycling involves metal refining and recovery of transition metals, which requires a lot of manpower and equipment, and the recycling cost is high. Low-cost, environmentally friendly, and efficient recovery of rare metals such as cobalt, nickel, manganese, and titanium is a severe challenge currently facing waste battery recycling. Directly using its post-transition metal resources to prepare efficient non-precious metal electrocatalysts can not only solve the problem of low-cost, environmentally friendly, and efficient recovery of waste batteries, but also solve the problem of high cost of precious metal catalysts in electrolyzers. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a method for recycling waste lithium-ion battery electrode materials to prepare multi-heterojunction electrocatalysts, multi-heterojunction electrocatalysts and their applications. The present invention directly converts the late transition metal resources in waste lithium-ion battery electrodes into high-efficiency electrolytic cell electrolysis water electrocatalysts, which is a promising way to promote the sustainable and green utilization of materials, but a simple and efficient transition technology still needs to be developed. And the structural composition of the synthesized material and the heterogeneous surface interface can be regulated by adjusting the ratio of several electrode materials and the temperature to improve its electrocatalytic activity for oxygen evolution reaction.

[0004] The first object of the present invention is to provide a method for recycling waste lithium-ion battery electrode materials to prepare multi-heterojunction electrocatalysts, comprising the following steps:

[0005] Provide an electrode material recycled from waste lithium-ion battery electrodes;

[0006] The recovered electrode material is heated to remove the binder and the conductive agent, then ball-milled, and then a solvent and a nitrogen-containing polymer are added and stirred to obtain a spinning solution;

[0007] The obtained spinning solution is subjected to high-voltage electrostatic spinning to obtain a spinning film;

[0008] The spun film is placed in a heating container and subjected to a gradient temperature increase treatment under an inert atmosphere to obtain the multi-heterojunction electrocatalyst.

[0009] In some embodiments of the present invention, the electrode material includes a positive electrode material and / or a negative electrode material.

[0010] The electrode material includes a ternary material of nickel-cobalt-lithium manganese oxide LiNix CoyMn 1-x-y O2, lithium iron phosphate, lithium titanate or one or more combinations thereof, wherein x ranges from 1 to 9, and y ranges from 1 to 5. Further, lithium nickel cobalt manganese oxide and lithium iron phosphate are positive electrode materials, and lithium titanate is negative electrode material.

[0011] In some embodiments of the present invention, the mass ratio of the electrode material to the solvent and the nitrogen-containing polymer is (3-15):1.

[0012] In some embodiments of the present invention, the nitrogen-containing polymer includes one or more of polyacrylonitrile, polysilazane, and carbon nitride, and the nitrogen-containing polymer provides a nitrogen source and a carbon source for the pyrolysis of the electrode material spinning film;

[0013] The heating temperature is 300-1000°C and the heating time is 30-300min;

[0014] The ball milling time is 5 to 80 minutes.

[0015] In some embodiments of the present invention, the parameters of high voltage electrospinning are: voltage range 10-30 kV.

[0016] In some embodiments of the present invention, the thickness of the spun film is 5 to 500 microns.

[0017] In some embodiments of the present invention, the non-reactive gas in the inert atmosphere is nitrogen and / or argon.

[0018] Among them, the parameters of gradient heating are: heating at 100-350°C for 20-120min, then heating at 800-1200°C for 0.5-5h, and the heating rate is 2-10°C / min; compared with the complete destruction of the one-dimensional microstructure and macroscopic film structure caused by direct heating, the one-dimensional microstructure and macroscopic film structure of the spun film remain intact after gradient heating.

[0019] In some embodiments of the present invention, the spun film is subjected to vacuum drying treatment at a drying temperature of 40 to 120°C.

[0020] The second object of the present invention is to provide a heterojunction electrocatalyst prepared by the method, wherein the electrocatalyst has multiple heterostructure interfaces, and the more heterostructure interfaces, the more catalytic active sites and the higher the activity.

[0021] The third object of the present invention is to provide an application of the electrocatalyst in the oxygen evolution reaction (OER) of water electrolysis.

[0022] The above technical solution of the present invention has the following advantages compared with the prior art:

[0023] The present invention proposes direct carbon thermal reduction of waste battery electrode materials, from Ni4N / Co 5.47 N / MnO, Ni4N / Co 5.47 N / MnO / Fe2P, Ni4N / Co 5.47 N / MnO / Fe2P / TiN, Ni4N / Co 5.47 Nanoparticles such as N / MnO / TiN and Fe2P / TiN are loaded on porous nitrogen-doped carbon fibers (NCF) to form heterojunctions as highly active electrocatalysts for oxygen evolution reaction (OER). A built-in electric field is spontaneously formed at the interface of the heterojunction of the present invention, which is beneficial to the synergistic effect of the interface, thereby accelerating the charge transfer in the catalyst and enhancing its conductivity. At the same time, the directional movement of electrons induces the local charge rearrangement at the heterojunction interface, enhancing the heterojunction catalyst for OH - adsorption.

[0024] The preparation method provided by the present invention avoids the complicated separation process of different metals and can quickly synthesize the catalyst. More importantly, the optimized material has a rich heterogeneous structure, which promotes the rapid transfer of electrons / protons. Therefore, as the optimized OER electrocatalyst Ni4N / Co 5.47 N / MnO / NCF, Ni4N / Co 5.47 N / MnO / Fe2P / NCF and Ni4N / Co 5.47 N / MnO / Fe2P / TiN / NCF at 10 mA cm -2 The overpotentials under 10 mA cm -2 conditions, and excellent stability.

[0025] The invention has the characteristics of simple synthesis, convenient operation, wide application range, etc., and the preparation conditions are mild, the method is simple, no special equipment is required, and the cost is relatively low, paving the way for the rapid and efficient recycling of waste batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0027] Figure 1 The present invention is a flow chart of the method of using waste lithium-ion battery electrode materials as electrocatalysts.

[0028] Figure 2 It is the Fe2P / NCF heterojunction LSV of the catalyst obtained in Example 1 of the present invention.

[0029] Figure 3This is the XRD spectrum of the Fe2P / NCF heterojunction of the catalyst obtained in Example 1 of the present invention.

[0030] Figure 4 The Ni4N / Co catalyst obtained in Example 2 of the present invention 5.47 N / MnO / NCF heterojunction LSV.

[0031] Figure 5 This is the TiN / NCF mass junction LSV of the catalyst obtained in Example 3 of the present invention.

[0032] Figure 6 The Ni4N / Co catalyst obtained in Example 4 of the present invention 5.47 N / MnO / Fe2P / NCF heterojunction LSV.

[0033] Figure 7 The Ni4N / Co catalyst obtained in Example 5 of the present invention 5.47 N / MnO / TiN / NCF heterojunction LSV.

[0034] Figure 8 The Ni4N / Co catalyst obtained in Example 6 of the present invention 5.47 N / MnO / Fe2P / TiN / NCF heterojunction LSV.

[0035] Fig. 9 This is the Fe2P / NCF heterojunction TEM of the catalyst obtained in Example 1 of the present invention.

[0036] Fig.10 This is the element distribution diagram of the Fe2P / NCF heterojunction of the catalyst obtained in Example 1 of the present invention.

[0037] Fig.11 This is the Ni4N / NCF heterojunction XRD of the catalyst obtained in Example 3 of the present invention.

[0038] Fig.12 The catalyst obtained in Example 2 of the present invention is Ni4N / C O5.47 Nitrogen element XPS of N / MnO / NCF heterojunction.

[0039] Fig.13 The Ni4N / Co catalyst obtained in Example 2 of the present invention 5.47 N / MnO / NCF element distribution diagram.

[0040] Fig.14 The Ni4N / Co catalyst obtained in Example 5 of the present invention 5.47 Element distribution diagram of N / MnO / TiN / NCF heterojunction.

[0041] Fig.15The Ni4N / Co catalyst obtained in Example 6 of the present invention 5.47 Long-term stability of N / MnO / Fe2P / TiN / NCF.

[0042] Fig.16 is 10 mA cm corresponding to the embodiment of the present invention -2 The oxygen evolution overpotential at .

[0043] Fig.17 The electrocatalyst Ni4N / Co obtained by directly heating the corresponding comparative example 2 of the present invention is 5.47 N / MnO / NC and electrocatalyst Ni4N / Co obtained by gradient heating 5.47 Comparison of appearance and morphology of N / MnO / NCF.

[0044] Fig.18 The catalyst Ni4N / Co obtained in Comparative Example 2 of the present invention 5.47 10 mA cm for N / MnO / NC -2 The oxygen evolution overpotential at . DETAILED DESCRIPTION

[0045] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0046] Example 1

[0047] This embodiment provides a method for using waste battery electrode materials as electrocatalysts, which is as follows:

[0048] Step 1: Extract the lithium iron phosphate (LFP) electrode material of the waste lithium-ion battery and heat it at 700°C in air for 120 minutes to remove the binder and conductive agent.

[0049] Step 2: Put 0.5 g of lithium iron phosphate positive electrode material obtained in step 1 into a ball mill and mill for 40 minutes, then add 8 mL of DMF and 1 g of polyacrylonitrile and stir overnight to prepare a spinning solution.

[0050] Step 3: The spinning solution obtained in step 2 is loaded into a needle for 25 kV high-voltage electrospinning, and the prepared spinning film is dried in a vacuum oven at 60° C. overnight.

[0051] Step 4: Place the dried spun film obtained in step 3 in a tubular furnace and perform a gradient heating process under argon conditions. The gradient heating parameters are: first heating at 250°C for 1h, then heating at 1000°C for 3h, and the heating rate is 5°C / min. Finally, Fe2P / NCF heterojunction electrocatalyst is prepared. Synthesis steps are shown in Figure 1The obtained materials were characterized by the results, see Figure 2 and Figure 3 and Fig. 9 and Fig.10 and 16 As can be seen from the figure, the Fe2P / NCF heterojunction was successfully synthesized. Compared with the commercial ruthenium dioxide oxygen evolution catalyst, the Fe2P / NCF heterojunction exhibited better performance, and its oxygen evolution overpotential was 238mV.

[0052] Example 2

[0053] This embodiment provides a method for using waste lithium-ion battery electrode materials as an electrocatalyst, which is as follows:

[0054] Step 1: Use the waste lithium-ion battery electrode material NCM523 (LiNi 0.5 Co 0.2 Mn 0.3 O2) was extracted and heated at 700℃ in air for 120min to remove the binder and conductive agent.

[0055] Step 2: 0.6 g NCM523 (LiNi 0.5 Co 0.2 Mn 0.3 The O2) ternary electrode material was placed in a ball mill for 40 minutes, and then 5 mL of dimethylacetamide and 1 g of polyacrylonitrile were added and stirred overnight to prepare a spinning solution.

[0056] Step 3: The spinning solution obtained in step 2 is loaded into a needle for 25 kV high-voltage electrospinning, and the prepared spun film is dried in a vacuum oven at 60° C. overnight.

[0057] Step 4: The dried spun film obtained in step 3 is placed in a tubular furnace and subjected to a gradient heating treatment under argon conditions. The gradient heating parameters are: first heated at 350°C for 0.5h, then heated at 800°C for 3h, and the heating rate is 5°C / min, and finally Ni4N / Co 5.47 N / MnO / NCF. Synthesis steps are shown in Figure 1 The obtained materials were characterized by the results, see Figure 4 , Fig.12 and Fig.13 , it can be seen from the figure that Ni4N / Co 5.47 Successful synthesis of N / MnO / NCF heterojunction.

[0058] The obtained Ni4N / Co 5.47 The oxygen evolution performance of N / MnO / NCF electrocatalyst was tested. The experimental results are shown in Fig.16 As shown in the figure, compared with the commercial ruthenium dioxide oxygen evolution catalyst, Ni4N / Co5.47 The N / MnO / NCF heterojunction exhibits considerable oxygen evolution performance with an oxygen evolution overpotential of 271 mV.

[0059] Example 3

[0060] This embodiment provides a method for using waste battery electrode materials as electrocatalysts, which is as follows:

[0061] Step 1: Extract lithium titanate (LTO), the negative electrode material of waste lithium-ion batteries, and heat it at 700°C in air for 120 minutes to remove the binder and conductive agent.

[0062] Step 2: Put 0.7 g of the electrode material LTO obtained in step 1 into a ball mill and mill it for 40 minutes, then add 10 mL of DMSO and 0.8 g of polysilazane and stir overnight to prepare a spinning solution.

[0063] Step 3: The spinning solution obtained in step 2 is loaded into a needle for 25 kV high-voltage electrospinning, and the prepared spinning film is dried in a vacuum oven at 60° C. overnight.

[0064] Step 4: Place the dried spun film obtained in step 3 in a tubular furnace and perform a gradient heating treatment under argon conditions. The gradient heating parameters are: first heating at 250°C for 1h, then heating at 900°C for 3h, and the heating rate is 5°C / min, and finally a TiN / NCF heterojunction electrocatalyst is prepared. Synthesis steps are shown in Figure 1 The obtained materials were characterized by the results, see Figure 5 and Fig.11 and Fig.16 As can be seen from the figure, the TiN / NCF heterojunction was successfully synthesized. Compared with the commercial ruthenium dioxide oxygen evolution catalyst, the TiN / NCF heterojunction exhibited better performance, and its oxygen evolution overpotential was 265mV.

[0065] Example 4

[0066] This embodiment provides a method for using waste battery electrode materials as electrocatalysts, which is as follows:

[0067] Step 1: Use the waste lithium-ion battery electrode material NCM523 (LiNi 0.5 Co 0.2 Mn 0.3 The ternary electrode material O2) was released and lithium iron phosphate (LFP) was extracted, and the binder and conductive agent were removed by heating at 700°C in air for 120 min.

[0068] Step 2: Add 0.5 g NCM523 (LiNi 0.5 Co 0.2 Mn0.3 The ternary electrode material O2) and 0.5 g lithium iron phosphate (LFP) were placed in a ball mill in a mass ratio of 1:1 and ball milled for 40 minutes, and then 8 mL DMF and 1 g polyacrylonitrile were added and stirred overnight to prepare a spinning solution.

[0069] Step 3: The spinning solution obtained in step 2 is loaded into a needle for 25 kV high-voltage electrospinning, and the prepared spinning film is dried in a vacuum oven at 80° C. overnight.

[0070] Step 4: The dried spun film obtained in step 3 is placed in a tubular furnace and subjected to a gradient heating treatment under argon conditions. The gradient heating parameters are: firstly heated at 250°C for 1 h, then heated at 1000°C for 3 h, and then heated at 1200°C for 0.5 h. The heating rate is 5°C / min, and finally Ni4N / Co is prepared. 5.47 N / MnO / Fe2P / NCF heterojunction electrocatalyst. Synthesis steps are shown in Figure 1 The obtained materials were characterized by the results, see Figure 6 As can be seen from the figure, Ni4N / Co 5.47 Successful synthesis of N / MnO / Fe2P / NCF heterojunction.

[0071] Performance test: The obtained Ni4N / Co 5.47 The performance of N / MnO / Fe2P / NCF heterojunction electrocatalyst was tested. The experimental results are shown in Fig.16 As shown in the figure, compared with the commercial ruthenium dioxide oxygen evolution catalyst, Ni4N / Co 5.47 The N / MnO / Fe2P / NCF heterojunction exhibits better performance, with an oxygen evolution overpotential of 237 mV.

[0072] Example 5

[0073] This embodiment provides a method for using waste battery electrode materials as electrocatalysts, which is as follows:

[0074] Step 1: Use the waste lithium-ion battery electrode material NCM523 (LiNi 0.5 Co 0.2 Mn 0.3 O2) ternary electrode material and lithium titanate (LTO) are extracted and heated at 700°C in air for 120 min to remove the binder and conductive agent.

[0075] Step 2: 0.4 g NCM523 (LiNi 0.5 Co 0.2 Mn 0.3O2) ternary electrode material and 0.4g lithium titanate (LTO) were put into a ball mill in a mass ratio of 1:1 and ball milled for 40 minutes, and then 8mL DMF and 1g polyacrylonitrile were added and stirred overnight to prepare a spinning solution.

[0076] Step 3: The spinning solution obtained in step 2 is loaded into a needle for 25 kV high-voltage electrospinning, and the prepared spinning film is dried in a vacuum oven at 60° C. overnight.

[0077] Step 4: The dried spun film obtained in step 3 is placed in a tubular furnace and subjected to a gradient heating treatment under argon conditions. The gradient heating parameters are: first heated at 250°C for 1 h, then heated at 1000°C for 3 h, and the heating rate is 5°C / min. Finally, Ni4N / Co 5.47 N / MnO / TiN / NCF heterojunction electrocatalyst. Synthesis steps are shown in Figure 1 The obtained materials were characterized by the results, see Figure 7 and Fig.14 , it can be seen from the figure that the distribution of nickel, cobalt, manganese, titanium and nitrogen elements completely overlaps, indicating that Ni4N / Co 5.47 Successful synthesis of N / MnO / TiN / NCF heterojunction.

[0078] Performance test: The obtained Ni4N / Co 5.47 The performance of N / MnO / TiN / NCF heterojunction electrocatalyst was tested. The experimental results are shown in Fig.16 As shown in the figure, compared with the commercial ruthenium dioxide oxygen evolution catalyst, Ni4N / Co 5.47 The N / MnO / TiN / NCF heterojunction exhibits more outstanding performance with an oxygen evolution overpotential of 183 mV.

[0079] Example 6

[0080] This embodiment provides a method for using waste battery electrode materials as electrocatalysts, which is as follows:

[0081] Step 1: Use the waste lithium-ion battery electrode material NCM523 (LiNi 0.5 Co 0.2 Mn 0.3 O2) ternary electrode materials and lithium iron phosphate (LFP) and lithium titanate (LTO) are extracted and heated at 700°C in air for 120 min to remove the binder and conductive agent.

[0082] Step 2: 0.3 g NCM523 (LiNi 0.5 Co 0.2 Mn 0.3O2) ternary electrode material and 0.3g lithium iron phosphate (LFP) and 0.3g lithium titanate (LTO) in a mass ratio of 1:1:1 were put into a ball mill for 40 minutes, and then 10mL DMF and 1g polyacrylonitrile were added and stirred overnight to prepare a spinning solution.

[0083] Step 3: The spinning solution obtained in step 2 was loaded into a needle for 25 kV high-voltage electrospinning, and the prepared spinning film was dried in a vacuum oven at 100° C. overnight.

[0084] Step 4: The dried spun film obtained in step 3 is placed in a tubular furnace and subjected to a gradient heating treatment under argon conditions. The gradient heating parameters are: first heated at 250°C for 1 h, then heated at 1000°C for 3 h, and the heating rate is 5°C / min. Finally, Ni4N / Co 5.47 N / MnO / Fe2P / TiN / NCF heterojunction electrocatalyst. Synthesis steps are shown in Figure 1 The obtained materials were characterized and the obtained Ni4N / Co 5.47 The oxygen evolution performance of N / MnO / Fe2P / TiN / NCF heterojunction electrocatalyst was tested. The experimental results are shown in Figure 8 and Fig.15 and Fig.16 , it can be seen from the figure that Ni4N / Co 5.47 Compared with commercial ruthenium dioxide oxygen evolution catalyst, Ni4N / Co 5.47 The N / MnO / TiN / NCF heterojunction exhibits more outstanding oxygen evolution performance, with an oxygen evolution overpotential of 181 mV and no performance degradation after 45 hours of operation.

[0085] Comparative Example 1

[0086] Commercial ruthenium dioxide (RuO2) was purchased as a standard oxygen evolution electrocatalyst for performance comparison. The commercial ruthenium dioxide standard electrocatalyst was purchased for oxygen evolution performance testing. The specific experimental results are shown in Fig.16 , and its oxygen evolution overpotential is 269mV.

[0087] Comparative Example 2

[0088] This comparative example provides a method for using waste lithium-ion battery electrode materials as electrocatalysts, which is as follows:

[0089] Step 1: Use the waste lithium-ion battery electrode material NCM523 (LiNi 0.5 Co 0.2 Mn 0.3 O2) was extracted and heated at 700℃ in air for 120min to remove the binder and conductive agent.

[0090] Step 2: 0.6 g NCM523 (LiNi 0.5 Co 0.2 Mn 0.3 The O2) ternary electrode material was placed in a ball mill for 40 minutes, and then 5 mL of dimethylacetamide and 1 g of polyacrylonitrile were added and stirred overnight to prepare a spinning solution.

[0091] Step 3: The spinning solution obtained in step 2 is loaded into a needle for 25 kV high-voltage electrospinning, and the prepared spun film is dried in a vacuum oven at 60° C. overnight.

[0092] Step 4: The dried spun film obtained in step 3 is placed in a tubular furnace and directly heated under argon conditions at a heating rate of 5°C / min to finally produce Ni4N / Co 5.47 N / MnO / NC. Synthesis steps are the same as Figure 1 The obtained materials were characterized by the results, see Fig.17 , it can be seen from the figure that Ni4N / Co 5.47 The N / MnO / NC spinning film agglomerates during the direct heating process, and the microstructure is completely different from that of the gradient heating process, and the microscopic one-dimensional structure is destroyed. 5.47 The oxygen evolution performance of N / MnO / NC electrocatalyst was tested. The experimental results are shown in Fig.18 As shown in the figure, the commercial ruthenium dioxide oxygen evolution catalyst and the electrocatalyst Ni4N / Co obtained by gradient heating 5.47 Compared with N / MnO / NC, Ni4N / Co 5.47 N / MnO / NC exhibits relatively poor oxygen evolution performance, with an oxygen evolution overpotential of 378 mV.

[0093] Electrochemical testing

[0094] (i) Material preparation: Nickel foam (NF) was first pretreated with 1 mol / L HCl to remove impurities such as surface oxides and grease, and was further cut into 1.2 × 1 cm pieces.

[0095] 5 mg of the catalyst obtained in Example 6 and Comparative Example 1 and 30 ul of nafion were mixed into 970 ul of anhydrous ethanol and ultrasonicated for 30 min to obtain a catalyst solution. 200 ul of the catalyst solution was drop-coated on the treated nickel foam and then dried in an oven at 60°C for 1 hour for standby use.

[0096] (i) Electrocatalytic measurement of OER: Electrochemical measurements were performed using a conventional three-electrode system on an electrochemical workstation (CHI 760E). Hg / HgO was used as the reference electrode, a carbon rod was used as the counter electrode, and the catalyst-loaded nickel foam obtained in the example was used as the working electrode. The scan rate was 5 mV in 1 M potassium hydroxide solution.-1 The OER activity was evaluated by linear sweep voltammetry (LSV) when the current response was 0.04 V. The stability of the OER was tested by timing the current response. The experimental results are shown in Fig.15 , it can be seen from the figure that Ni4N / Co 5.47 The performance of N / MnO / Fe2P / TiN / NCF hardly decays after 45h.

[0097] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A method for recycling waste lithium-ion battery electrode materials to prepare multi-heterojunction electrocatalysts, characterized in that: The following steps are involved: Provide an electrode material recycled from waste lithium-ion battery electrodes; The recovered electrode material is heated to remove the binder and the conductive agent, then ball-milled, and then a solvent and a nitrogen-containing polymer are added and stirred to obtain a spinning solution; The obtained spinning solution is subjected to high-voltage electrostatic spinning to obtain a spinning film; The spun film is placed in a heating container and subjected to a gradient temperature increase treatment under an inert atmosphere to obtain the multi-heterojunction electrocatalyst.

2. The method according to claim 1, characterized in that The electrode material includes a positive electrode material and / or a negative electrode material.

3. The method according to claim 1, characterized in that The mass ratio of the electrode material to the nitrogen-containing polymer is (3-15):1; The solvent is selected from one or more of N,N-dimethylformamide, dimethylacetamide and dimethyl sulfoxide.

4. The method according to claim 1, characterized in that: The nitrogen-containing polymer includes one or more of polyacrylonitrile, polysilazane, and carbon nitride; The heating temperature is 300-1000°C and the heating time is 30-300min; The ball milling time is 5 to 80 minutes.

5. The method according to claim 1, characterized in that The parameters of high voltage electrospinning are: voltage range 10-30kV.

6. The method according to claim 1, characterized in that The thickness of the spinning film is 5 to 500 microns.

7. The method according to claim 1, characterized in that The inert gas in the inert atmosphere is nitrogen and / or argon; Gradient heating parameters: heating at 100-350°C for 20-120 min, then heating at 800-1200°C for 0.5-5 h, with a heating rate of 2-10°C / min.

8. The method according to claim 1, characterized in that: The spun film is subjected to vacuum drying treatment at a drying temperature of 40 to 120°C.

9. A heterojunction electrocatalyst, characterized in that: The electrocatalyst prepared by the method according to any one of claims 1 to 8 has multiple heterogeneous structural interfaces, and the more heterogeneous interfaces there are, the more catalytic active sites there are and the higher the activity.

10. Use of the electrocatalyst according to claim 9 in oxygen evolution reaction (OER) by electrolysis of water.